INFLUENCER'S EFFECT ON SOCIOLEGAL AND ECONOMIC DEVELOPMENT IN A DEVELOPING COUNTRY, ESPECIALLY IN INDONESIA - Nurcahyo, Nanang (Progressive Law Review, 2021)
The development of the era is much influenced by several factors, ranging from technological developments, economics and dynamic regulations. but of all these factors are much influenced by the thoughts or influences of world leaders. there are world leaders in politics, religion, celebrities and wealthy businessmen who can influence developing countries. With this influence, it will have an impact on several aspects of human life, so that it will cause a massive change in various aspects of life